PENGARUH PERSEPSI KARYAWAN TERHADAP TATA KELOLA KEUANGAN PADA KSP KOPDIT PINTU AIR ROTAT - Yorina Sari, Imakulata; Rengga, Andreas; Yuneti, Katharina (Jurnal Projemen UNIPA, 2025)
This research aimed to determine de influence of employee perception on financial governance at KSP Kopdit Pintu Air Rotat. This research used a descriptive quantitative method with a survey approach. The population consisted of all 69 permanent employees of KSP Kopdit Pintu Air Rotat, and the entire population was used as the sample through a saturated sampling techineque. Primari data were collected using a questionnaire and analyzed using descriptive statistics and simple linear regression. The results showed that employee perception has a positive and significant effect on financial governance, with a coefficient of 59.3%. This means that the more positive the employees’ perception, the better the cooprerative’s financial governance.